Exploring Students’ Experiences with Teacher-Guided YouTube Learning for Vocabulary Mastery - Hasanah, Rizki; Nirwanto, Rahmadi; Mirza, Akhmad Ali (Journal of English Language and Education, 2025)
This study explores students' experiences in utilizing YouTube for vocabulary mastery at MA Hidayatul Insan Palangka Raya. Traditional methods often cause disengagement, while YouTube offers an interactive alternative through multimedia content. This research addresses: (1) How do students experience learning vocabulary through YouTube? (2) What challenges do they face? Using a qualitative phenomenological approach, data were collected via interviews with 15 students. Findings reveal that YouTube enhances engagement, motivation, and vocabulary retention through visual and contextual learning. Teachers support learning by structuring lessons, pausing videos for explanations, and incorporating interactive activities. Additionally, students use YouTube independently for self-directed learning. However, challenges include internet access issues and difficulty identifying reliable content. This study highlights YouTube’s potential as an effective vocabulary-learning tool when combined with teacher guidance and structured activities.